Narrative Structure in Souad: Representing Female Identity in Arabic Sinema - Muchammad Naufal Fauqi Adhiya; Wildan Taufiq; Mohammad Rosyid Ridho (Sekolah Tinggi Agama Islam Darul Ulum Banyuanyar Pamekasan, 2026)
The film Souad (2021) by Ayten Amin represents the complexity of young Egyptian women's lives caught between patriarchal cultural demands and the expansion of digital space. This study aims to describe the narrative structure of Souad through Algirdas Julien Greimas's narrative semiotic approach, encompassing the actantial scheme, functional structure, and spatial-temporal isotopy. The research employs a descriptive qualitative method with documentation techniques based on repeated observation of the film, scene recording, and analysis grounded in Greimas's actantial model. The findings show that the film contains two interconnected actantial trajectories: that of Souad and that of Rabab. Souad functions as the subject seeking recognition, validation, and an ideal identity through social media, yet fails due to the pressure of the family's socio-religious norms and an unfulfilling virtual relationship. Rabab, by contrast, emerges as a new subject who continues the plot with the goal of uncovering the cause of her sister's death through a direct meeting with Ahmed. This subject shift constitutes the narrative's distinctive feature, departing from the conventional actantial pattern. Social media functions simultaneously as an adjuvant and as a space that produces identity conflict, while spatial and temporal isotopy reveals the tension between the protagonist's real and digital lives. The findings indicate that Souad critiques the limited space for women's expression within patriarchal society through a complex narrative structure.